Development Of Islamic Religious Education Curriculum Design At Miftahul Ulum School, Retok Village, Kubu Raya Regency - Syaiful, Syaiful; Abdurrahman, Abdurrahman (JSP: Jurnal Studi Pesantren, 2025)
Islamic Religious Education (IRE) has a vital role in shaping students’ character and morals. Miftahul Ulum School in Retok Village, Kubu Raya Regency, as an Islamic-based institution, faces challenges in developing a curriculum that is both relevant to contemporary needs and rooted in Islamic values. This study aims to develop an innovative and contextual IRE curriculum design through an analysis of existing practices and stakeholder needs. This research uses a qualitative approach with a case study design and a constructivist paradigm. Data were collected through in-depth interviews with teachers, administrators, and parents, classroom observations, and document analysis. Data analysis followed the interactive model of Miles and Huberman, including data collection, reduction, display, and conclusion drawing. Triangulation was applied to ensure data validity. The findings indicate that the current IRE curriculum requires better integration between the national curriculum and pesantren traditions, the application of more interactive and experiential learning methods, and the development of comprehensive evaluation systems. Key gaps were found in the integration of spiritual practices, the use of technology in learning, and the assessment of affective and psychomotor domains. Based on these findings, this study proposes an integrated curriculum model consisting of three main components: integration of national and pesantren-based curricula, active learning methods such as project-based and collaborative learning, and competency-based evaluation covering cognitive, affective, and psychomotor aspects.